O contrato de trabalho intermitente e a garantia dos direitos do empregado ao final de cada período de prestação de serviço - Filho, Tiago Tito Pereira de Carvalho (Universidade Federal do Tocantins, 2021)
Inserted in the Brazilian legal system on the pretext of making labor relations more flexible and creating more jobs, the Intermittent Employment Contracts have several controversial points that are discussed by experts in the labor area. In this work, focus will be given to the end-of-service payment owed to intermittent employees, analyzing if the normative provisions applicable to this contractual modality ensures the payment of owed employee earnings. A biographic review in specialized studies was conducted and definitions were sought regarding the amount owed and their payment forms. Grounded in established premises and using deductive reasoning, conclusion was reached in order to answer whether the employee rights would be guaranteed or not. A qualitative method was adopted, since the final points were brought together after a process based on understanding, analyzing and interpreting the theme exposed throughout this article. The final observations conclude that Intermittent Contracts can lead to situations in which the quotas established by law are not paid due to the lack of suitability of the rules to the features of the studied contractual type, indicating that a legislative or jurisprudential integration is convenient to fill existing gaps.